1957
DOI: 10.1346/ccmn.1957.0060118
|View full text |Cite
|
Sign up to set email alerts
|

Further Observations on the Morphology of Chrysotile and Halloysite

Abstract: Electron microscope studies of chrysotile show that tubes are present in bulk specimens and that these tubes commonly have fuzzy, amorphous-looking material on both the inside and outside. Similar material is associated with synthetic chrysotile and has been noted previously in halloysite specimens. The existence of such material between and within the tubes, together with apparent irregularities in size, shape and packing of tubes, explains the apparent discrepancy between the measured density of bulk samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

1960
1960
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…It is noted that the tilting of the two sets of the 4.5 A fringes are asymmetrical about the fibre axis with an angular difference of a few degrees. This type of growth pattern seems to correspond to the cone-in-cone pattern which was reported by Bates & Comer (1957).…”
Section: (C) Growth Patternssupporting
confidence: 82%
See 1 more Smart Citation
“…It is noted that the tilting of the two sets of the 4.5 A fringes are asymmetrical about the fibre axis with an angular difference of a few degrees. This type of growth pattern seems to correspond to the cone-in-cone pattern which was reported by Bates & Comer (1957).…”
Section: (C) Growth Patternssupporting
confidence: 82%
“…In earlier X-ray studies, however, single crystals were not available, while in subsequent studies made on single crystals (individual fibrils), by means of electron microscopy combined with selected area electron diffraction, the instrumental resolution was not high enough to resolve the fine structures (Honjo & Mihama, 1954;Zussman, Brindley & Comer, 1957;Bates & Comer, 1957). Recently, it has become possible to observe lattice planes in the individual fibrils of chrysotile (FermindezMor~in, 1966;Yada, 1967), and it has been found, for example, that the circumferential lattice images observed in the cross-section of a fibril show a spiral or multi-spiral structure.…”
Section: Introductionmentioning
confidence: 99%
“…This complex was both stable under evacuation and tubular in morphology when examined by electron microscopy. Davis et al (1950), Taggart et al (1955, Bates and Comer (1959), and other workers have reported studies of dehydrated endellite preparations and in general concur that the particles observed are generally tubular. No particular mutual orientation of particles has been reported, although some flattening of the tubes was observed in a number of cases.…”
Section: Previous Determinations Of the Morphology Of Endellitementioning
confidence: 60%
“…Scroll nanotubes were discovered during electron microscopy studies of the naturally occurring minerals chrysotile and halloysite (Bates et al, 1950;Bates, 1957;Yada, 1967Yada, , 1971Yada & Iishi, 1977) in the 1950s. Later it was shown that a huge variety of scroll nanotubes with different chemical composition can be synthesized by various routes; up to now scroll nanotubes made of carbon (Bacon, 1960;Ruland et al, 2003;Shioyama & Akita, 2003;Chuvilin et al, 2009;Xie et al, 2009;Schaper, Hou et al, 2011), BN (Hwang & Suh, 2014), WS 2 (Li et al, 2002), TbS-CrS 2 (Panchakarla et al, 2016), SnS/ SnS 2 (Radovsky et al, 2011(Radovsky et al, , 2012, PbO (Shi et al, 2008), SrAl 2 O 4 (Ye et al, 2006), Ca 2 Nb 3 O 10 (Ma et al, 2004), K 4 Nb 6 O 17 (Saupe et al, 2000;Du et al, 2004;Tong et al, 2006;Adireddy et al, 2013), VO x (Krumeich et al, 1999;Muhr et al, 2000;Rostamzadeh et al, 2016), MnO 2 (Ma et al, 2004;Wang & Li, 2004), Mg 3 Si 2 O 5 (OH) 4 , Ni 3 Si 2 O 5 (OH) 4 (Krasilin & Gusarov, 2015;Krasilin et al, 2016Krasilin et al, , 2017 and Ruddlesden-Popper perovskites (Schaak & Mallouk, 2000) have been synthesized.…”
Section: Introductionmentioning
confidence: 99%